Lucky night : a novel - Kennedy, Eliza, 1974- (Crown, 2025)
"A couple, after six years of casual sex, are finally spending a night together. Twist? They are married to other people. A fire traps a couple in their hotel room and forces them to confront the lies they've told their spouses, each other, and themselves"--